Asymmetric ZnPc–TEG photosensitizers: the effect of Pc substitution on phototoxicity. Issue 45 (4th November 2015) - Muli, Dominic K.; Rajaputra, Pallavi; You, Youngjae; McGrath, Dominic V.
Graphical abstract: Abstract: Asymmetric zinc phthalocyanine (ZnPc) isomers with triethylene glycol (TEG) moieties in the peripheral (1a ) and non-peripheral (1b ) substitution were designed, synthesized, characterized, and their phototoxicity on colon-26 cells evaluated. TEG moieties as water solubilizing groups were incorporated at peripheral or non-peripheral positions to investigate the effect of their position on the Pc on the photodynamic activity. UV/vis analyses indicated a small red-shifting of the Q band of the non-peripheral ZnPc–TEG 1b (ca. 4 nm) relative to 1a in dichloromethane and THF. n -Octanol/pH 7.4 buffer partition coefficients revealed that 1b was marginally more hydrophilic than 1a with log D 7.4 values of 2.44 and 2.46, respectively. Fluorescence emission aggregation studies indicate that 1b is ca. 61% (DMSO) and 32% (phosphate buffer) less aggregated than the peripherally substituted ZnPc 1a suggesting that non-peripheral substitution decreased overall aggregation of the photosensitizers. Singlet oxygen generation studies are reported. Both ZnPc–TEGs showed negligible dark toxicity on colon 26 cells with 10 μM 1a and 1b . Irradiation (690 nm, 45 J/cm 2 ) of the cells produced an IC50 value >25 μM for 1a and an IC50 value between 1 and 5 μM for 1b . Overall, the non-peripheral isomer 1b was found to be more photodynamically active.